Vaccination in adults with chronic diseases and multimorbidity in Mexico: Analysis of the 2018-2022 ENSANUT - Lozano Keymolen, Daniel; Fierro Moreno, Eréndira; Vilchis Sotelo, María Miel (Horizonte Sanitario, 2025)
Objective: To analyze the prevalence of vaccination among people with diabetes mellitus, heart disease, or multimorbidity in Mexico in 2018 and 2022, using secondary data from two rounds of the National Health and Nutrition Survey. Materials and methods: Using data from probabilistic surveys representative of the Mexican population in 2018 and 2022, national vaccination rates were estimated by self-reporting against measles and rubella, tetanus, pneumococcal disease, and seasonal influenza in three age groups defined in the surveys. Binomial logistic regressions were used to calculate the propensities to receive the studied vaccines in people with diabetes, heart disease, or multimorbidity during the two years of the study. Results: In individuals aged 20 to 39, measles and rubella vaccination rates were around 30.0 percent, while in those aged 60 and older, seasonal influenza vaccination rates reached approximately 58.0 percent. Multimorbidity increases the likelihood of receiving any of the studied vaccines by 1.4 to 2.0 times in individuals aged 20 to 59 and 60 and older, compared to individuals without chronic diseases. Conclusions: Diabetes and multimorbidity are positively associated with a higher likelihood of having recommended vaccines in adulthood. The findings underscore the importance of strengthening vaccination strategies targeting people with chronic diseases, as well as improving registration and monitoring systems. Keywords: Vaccination; Multimorbidity; Chronic Diseases; Diabetes Mellitus; Heart Diseases.